Shaping of Regional Differences in Oligodendrocyte Dynamics by Regional Heterogeneity of the Pericellular Microenvironment - Sherafat, Amin; Pfeiffer, Friederike; Nishiyama, Akiko (Frontiers in Cellular Neuroscience, 2021)
Oligodendrocyte precursor cells (OPCs) are glial cells that differentiate into mature oligodendrocytes (OLs) generate new myelin sheaths. While OPCs are distributed uniformly throughout the gray and white matter in the developing and adult brain, those in white matter proliferate and differentiate into oligodendrocytes at a greater rate than those in gray matter. There is currently lack of evidence to suggest that OPCs comprise genetically and transcriptionally distinct subtypes. Rather, the emerging view is that they exist in different cell and functional states, depending on their location and age. Contrary to the normal brain, demyelinated lesions in the gray matter of multiple sclerosis brains contain more OPCs and OLs and are remyelinated more robustly than those in white matter. The differences in the dynamic behavior of OL lineage cells are likely to be influenced by their microenvironment. There are regional differences in astrocytes, microglia, the vasculature, and the composition of the extracellular matrix. We will discuss how the regional differences in these elements surrounding OPCs might shape their phenotypic variability in normal and demyelinated states.